STUDY OF DIRECT RELATIONSHIP DETERMINANTS ON THE SELECTION OF MUSYARAKAH MUTANAQISAH (MM) PRODUCTS - Bahari, Zakaria; Hatizal, Nor; Doktoralina, Caturida Meiwanto (International Journal of Supply Chain Management, 2019)
This study analyses the direct relationship of determinantsâ??both intrinsic and extrinsic factorsâ??affecting the selection of MusyÄrakat MutanÄqiá¹£at (MM) house financing products. Intrinsic factors include factors of confidence in sharia compliance value and factors regarding the knowledge level of potential customers. Extrinsic factors include MM product characteristics such as service quality, costs, product benefits and promotions. MM products are emphasised in this study because of their many benefits, including lowering the burden of customersâ?? monthly payloads, a relatively shorter monthly payment period and increased benefits and profits for both banks and customers. Data were collected from 100 MM customers in Malaysia via the Internet (Facebook) and analysed using Structural Equation Modeling (SEM-SMART PLS) and the Statistical Package of Social Sciences (SPSS) software. The findings show that only the factors of promotion and religious compliance are significant when selecting MM products; in fact, the influence of promotional factors had a greater impact than the influence of religious compliance. Therefore, Islamic banks are urged to increase their promotional strategies in order to provide information about the role of religious law in selecting Islamic banking products, thus helping customers choose MM products that satisfy their needs while also meeting religious demands.